New taxa of Hieracium (Asteraceae) from Mount Lesima and adjacent regions (Northern Apennine, Italy) - Gottschlich, Günter; Orsenigo, Simone (Phytotaxa, 2021)
Four species of Hieracium (H. lesimanum, H. scopolii, H. scopolioides and H. umbrophilum) and two subspecies of this genus (H. lachenalii subsp. zerbanum, H. prenanthoides subsp. penicense) from the Ligurian Apennines are described and illustrated.